Indigenous Technologies Fishing Settlement Response to Climate Change Variability’s in Southern Nigeria - C. O, Albert; B. I, Isife (Asian Journal of Agriculture and Rural Development, 2014)
The study focused on indigenous technologies used by fishermen in southern Nigeria as adaptation measures to climate change variability’s. Interview schedule was used to elicit information from sixty respondents in three (3) communities using simple random sampling technique. Percentage and mean scores were utilized for data analysis. The study established that the climate change experiences were: rise in sea level, rise in temperature, high wind, change in tidal pattern and frequent storms. The effects of climate change experiences on fishing include low fish catch, increase in boat mishap, reduced fish production and low growth rate of fishes. Indigenous technologies used as mitigating steps include building of bigger boats, the use of diverse fishing gears and observation of weather. These technologies had been very effective as mitigating steps. The study recommended mainly that modern weather forecasting facilities should be provided for the fishermen.